Effect of activated carbon on hydraulic properties of soil with multi-modal porosity - Wong, Feng Huan (Nanyang Technological University, 2021)
Slope failures induced by rainfall are not uncommon in Singapore. As pore water pressure builds up in unsaturated soils due to infiltration of water, it reduces the matric suction of the soil. In turn reduces the shear strength and leads to slope failures. Measures to avoid or mitigate these types of failures include holding regular inspections and rectifying defects to prevent soil erosion and water inflow during heavy rainfall as slope protection structures will deteriorate over time. However, there are other effective ways to improve the hydraulic property of the residual soil. One way is to strengthen soil-water retention behavior through the addition of various materials. Hydraulic properties of unsaturated soil above the water table have a major role in slope stability, which are known to be governed mainly by the soil-water characteristic curve (SWCC). Soils such as Sand-Kaolin show multi-modal characteristics in SWCC. Furthermore, the presence of porous materials such as activated carbon significantly affects the hydraulic properties of soils with multi-modal porosity.